2016
DOI: 10.24093/awej/vol7no4.20
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on Training in Writing Research Article for Publication

Abstract: The ability in scholar writing is pivotal for students at higher degree of education. They are demanded to be able to write the results of their research in the form of research article and are encouraged to publish it in reputable journals. The low self-efficacy, low ability in scholar writing, and lack of knowledge as well as experience are the factors hindering the students in writing their research articles. This study reports the students' perception on the training in writing research article for publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to Noortyani (2016), due to the insufficient knowledge and having the confusion in their mind, they become unable to express their ideas. Students find difficulties in arranging their ideas and thoughts properly, rather they also suffer from the level of confidence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Noortyani (2016), due to the insufficient knowledge and having the confusion in their mind, they become unable to express their ideas. Students find difficulties in arranging their ideas and thoughts properly, rather they also suffer from the level of confidence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, the departmental clubs can play a significant role as well. In the research of Noortyani (2016), suggests that training on the early period before conducting a research study, could help the students for topic selection. So, in that sense the university authorities can design the basic English language course by adding an extra topic for discussion on "how to select research topics" and teach the students the step-by-step process of topic selection.…”
Section: E Other Necessary Supportmentioning
confidence: 99%
“…These trends are present in graduate school and beyond. Noortyani (2016) highlights how students in developing countries face extra hurdles for writing internationally publishable academic articles in English. The students in her study lacked confidence in their language skills to express their ideas and in their knowledge to write in detail about certain subjects.…”
Section: A Publication Assignmentmentioning
confidence: 99%
“…According to Zhu (2004), in order to compose an academic piece of writing, students are required to demonstrate the following skills: "audience awareness, logical organization, paragraph development, clarity, sentence structure, grammar, and mechanics'' (p. 37). This task is challenging not only to EFL undergraduates, but also to EFL graduate students (Lavelle & Bushrow, 2007, as cited in Noortyani, 2016). Surprisingly, it is also reported that even native speakers of English face some difficulties producing pieces of academic writing (Al Fadda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Oliveira (2017, as cited in Obeso, 2019), a very limited number of studies have tackled the issue of monograph production the majority of which shed light on the problems undergraduate students face in the production of general academic pieces of writing (Lavelle & Bushrow, 2007;Nolan & Rocco, 2009;Al Fadda, 2012;Noortyani, 2016). The reasons behind these problems are to be reported as follows: (1) the complex nature of academic writing (Alfaki, 2015), (2) the lack of academic reading (Gorzycki et al, 2020), (3) the lack of research writing practice (Cahyono & Amrina, 2016), (4) the lack of motivation (Rabab'ah, 2003), and (5) the lack of research production knowledge (Nolan & Rocco, 2009).…”
Section: Introductionmentioning
confidence: 99%